Factors Associated With E-Cigarette Usage and the Reasons for Initiation Among Malaysian Adolescents. (October 2019) - Robert Lourdes, Tania Gayle; Abd Hamid, Hamizatul Akmal; Mohd Yusoff, Muhammad Fadhli; Rodzlan Hasani, Wan Shakira; Mat Rifin, Halizah; Saminathan, Thamil Arasu; Ab Majid, Nur Liana; Ling, Jane Miaw Yn; Ismail, Hasimah; Aris, Tahir
Electronic cigarettes (e-cigarettes) are handheld devices that deliver an aerosol by heating a solution made up of propylene glycol and/or glycerol with or without flavoring agents and nicotine. This nationwide cross-sectional survey examined factors associated with e-cigarette usage and reasons for its initiation among 13 162 Malaysian adolescents. Data from TECMA (Tobacco and E-Cigarette Survey among Malaysian Adolescents) were used. Nine percent of adolescents had used e-cigarettes in the past month. Males (adjusted odds ratio [aOR] = 4.08; 95% confidence interval [CI] = 3.36-4.95), 16 to 19 year olds (aOR = 2.64; 95% CI = 2.13-3.26), Malays (aOR = 2.25; 95% CI = 1.79-2.83), Sabah and Sarawak Bumiputeras (aOR = 2.25; 95% CI = 1.61-3.15), and cigarette smokers (aOR = 13.16; 95% CI = 11.14-15.54) were more likely to use e-cigarettes. Three main reasons for e-cigarette initiation among adolescents were its taste and smell, experimentation, and popularity. Sale of e-cigarettes with or without nicotine to people aged younger than 18 years should be banned. Flavored e-cigarettes should also be banned since there is evidence suggesting increased appeal among the younger generation.